Imprimitivity of locally finite, 1-ended, planar graphs - Širan, Jozef (Ars mathematica contemporanea, 2012)
Using results from group theory, we offer a concise proof of the imprimitivity of locally finite, vertex-transitive, 1-ended planar graphs, a result previously established by J. E. Graver and M. E. Watkins (2004) using graph-theoretical methods.
Keywords: co-compact group; end; graph theory; grupe; planar graph; primitive permutation group; ravninski grafi; residually finite group; teorija grafov